2018
DOI: 10.5902/2236117032254
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and ecotoxicological evaluation of the direct orange 26 dye degradation by Fenton and solar photo-Fenton processes

Abstract: The presence of color in textile effluents has been studied because of the need for more effective treatments. Therefore, advanced oxidative processes (AOP) have been used in the degradation of dyes, as well as in the conversion of organic matter. This study evaluated the degradation of the direct orange 26 textile dye by Fenton and photo-Fenton processes (with natural solar radiation). A statistical analysis, based on factorial 23 indicated the best working conditions, being: [H2O2] = 100 mg·L-1 and pH 3-4, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…By considering parameter 1/ b obtained by the BMG model, it is possible to observe that the maximum oxidation capacity of Fe 2+ -containing reactions ( R 2 > 0.9) increased in the presence of 3-HAA, e.g., the oxidation capacity of safranin T was almost three times greater in the presence of 3-HAA. Santana et al [42,43] showed the same upward trend in 1/ b on the decolorization kinetics of different dyes by Fenton systems using dihydroxybenzenes and gallic acid as redox mediators. Regarding parameter 1/ m , there were no significant changes in the initial degradation rates of dyes in the presence of 3-HAA.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…By considering parameter 1/ b obtained by the BMG model, it is possible to observe that the maximum oxidation capacity of Fe 2+ -containing reactions ( R 2 > 0.9) increased in the presence of 3-HAA, e.g., the oxidation capacity of safranin T was almost three times greater in the presence of 3-HAA. Santana et al [42,43] showed the same upward trend in 1/ b on the decolorization kinetics of different dyes by Fenton systems using dihydroxybenzenes and gallic acid as redox mediators. Regarding parameter 1/ m , there were no significant changes in the initial degradation rates of dyes in the presence of 3-HAA.…”
Section: Resultsmentioning
confidence: 79%
“…Therefore, the BMG model was more suitable to represent the Fe 2+ /H 2 O 2 system kinetics. In previous studies, the fitting of experimental kinetic data on two-stage decolorization of several dyes by classical Fenton reaction was better with the BMG model [34,39,40,41,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Nesse contexto, aponta-se o uso de processos oxidativos avançados (POA's) como uma solução para a contaminação de corpos hídricos pela presença de corantes advindos de efluentes têxteis. Partindo disso, tem-se que para o corante Reactive Blue, um dos mais utilizados na indústria têxtil, uma classe de POA's que vem apresentando resultados satisfatórios de degradação é a da fotocatálise, em especial o processo foto-Fenton (Santana, Nascimento & Napoleão et. al., 2017;Araujo, 2002).…”
Section: Introductionunclassified